"What a Welcome Relief" Attachment and Neuro-Affirming Parental Care in the Context of ADHD - Brown, Louise Elizabeth (Curtin University, 2023)
This thesis highlights the importance of the attachment relationship in the context of ADHD, and the need for, and importance of, an attachment-focused, neuro-affirming parenting approach. It also offers an alternative parenting approach that explicitly addresses this need, and importantly, provides preliminary evidence that the ADHD parenting program under construction is worthy of continued development, investment and evaluation.